Strategies In Learning Fluid Mechanics: A literature Review - Aliligay, Myrr Dane S.; Rendon, Justine Dave L.; Villarias, Chrysler John R.; Mercado, Justine C. (Future Science / FSH-PH Publications, 2022)
One of the broad and intricate subfields of physics is fluid mechanics. Learning techniques for students are an essential component of learning fluid mechanics because they increase their motivation to learn, enhance learning outcomes, and encourage active participation in class. An overview of the prior research was highlighted in this publication, and several fluid mechanics learning methodologies were looked at in this review. The study found that the majority of students performed well in group settings, particularly when fluid mechanics principles are used in practical settings, which is the most successful teaching method. The studies that were reviewed in this literature review demonstrated that offering students team-based experiential learning is the best way to inspire them to learn fluid mechanics and to recognize the value of doing so. Therefore, by developing ideas and putting them into practice through active exploration, students learn more.